Local Wisdom in Primary School Students' Directive Speech Acts - Nur Ihsan Halil; Agus Nasir; Hendri Yawan; Sarmadan Sarmadan (Politeknik Negeri Media Kreatif, 2023)
This research aims to investigate the directive speech acts in students’ communication of elementary schools as a form of local wisdom in the educational setting of Kolaka Regency. The interractive model proposed by Miles and Huberman was employed to analyse the data which consists of data reduction, data presentation, and a conclusion. The findings show that there are two types of directive speech atc performed by elementary school students which are 1) the speech act of commanding, and 2) the speech act of begging. Both forms of directive speech acts are affected by the cultural context which can be found in the form of clitics. The clitics are related to the local wisdom of the elementary students’ communication in Kolaka Regency in the forms, such as -ko, –mi and -na, as uttered in the form of lihatko, ayomi, pindahko, biarmi, siniko, jemputna